Pharmacodynamic Effects of Topical Omiganan in Patients With Mild to Moderate Atopic Dermatitis in a Randomized, Placebo‐Controlled, Phase II Trial - Tessa Niemeyer‐van der Kolk; Hein van derWall; Geretta K. Hogendoorn; Rianne Rijneveld; Sascha Luijten; Dirk C.J.G. vanAlewijk; Ellen H.A. van denMunckhof; Marieke L. deKam; Gary L. Feiss; Errol P. Prens; Jacobus Burggraaf; Robert Rissmann; et al. (Wiley, 2020)
Omiganan is an indolicidin analog with antimicrobial properties that could be beneficial for patients with atopic dermatitis. In this randomized, double‐blind, placebo‐controlled, phase II trial we explored the efficacy, pharmacodynamics, and safety of topical omiganan once daily in 36 patients with mild to moderate atomic dermatitis. Patients were randomized to apply topical omiganan 1%, omiganan 2.5%, or vehicle gel to one target lesion once daily for 28 consecutive days. Small but significant improvements in local objective SCORing Atopic Dematitis index and morning itch were observed in the omiganan 2.5% group compared with the vehicle gel group (−18.5%; 95% confidence interval, −32.9 to −1.0; P = 0.04; and −8.2; 95% confidence interval, −16.3 to −0.2; P = 0.05, respectively). A shift from lesional to nonlesional skin microbiota was observed in both omiganan treatment groups, in contrast to the vehicle group. Thus, treatment with topical omiganan improved dysbiosis in patients with mild to moderate atopic dermatitis, and small but statistically significant improvements in clinical scores were detected. Our findings warrant further exploration in future clinical trials.